Structural basis for mutually exclusive co-transcriptional nuclear cap-binding complexes with either NELF-E or ARS2 - Schulze, Wiebke Manuela (Nat Commun, 2017)
Pol II transcribes diverse classes of RNAs that need to be directed into the appropriate nuclear maturation pathway. All nascent Pol II transcripts are 5′-capped and the cap is immediately sequestered by the nuclear cap-binding complex (CBC). Mutually exclusive interactions of CBC with different partner proteins have been implicated in transcript fate determination. Here, we characterise the direct interactions between CBC and NELF-E, a subunit of the negative elongation factor complex, ARS2 and PHAX. Our biochemical and crystal structure results show that the homologous C-terminal peptides of NELF-E and ARS2 bind identically to CBC and in each case the affinity is enhanced when CBC is bound to a cap analogue. Furthermore, whereas PHAX forms a complex with CBC and ARS2, NELF-E binding to CBC is incompatible with PHAX binding. We thus define two mutually exclusive complexes CBC–NELF–E and CBC–ARS2–PHAX, which likely act in respectively earlier and later phases of transcription.